Estudo da codisposição de resíduos de fossas e tanques sépticos, com e sem a remoção prévia de gordura, no desempenho de tratamento de esgoto com reatores UASB - Peixoto, Aline Vieira (2013)
In Brazil, according to a national survey conducted by the Brazilian Institute of Geography and Statistics (IBGE, 2010), 44.8% of the municipalities use simplified domestic waste treatment systems such as septic tanks, rudimentary cesspools and dry pits. Such systems lead to the production of potentially polluting waste which requires suitable co-treatment. Several co-treatment alternatives have been proposed. The present study, which is part of the Program on Basic Sanitation Research (PROSAB), aimed to evaluate the interference caused by septage disposal from cesspools and septic tanks on the performance of the Upflow Anaerobic Sludge Blanket Reactor (UASB) in the city of Itumbiara- Goiás. The study took nine months and was divided into three distinct phases, in which the volumetric flow rate of wastewater from cesspools and septic tanks into the reactor ranged from 0.17% to 0.51%, displaying an intermediate phase of 0.34%.In the third phase, another fat flotation phase was added to the pre-treatment prior to discharge. During the study, we utilized all the waste volume from cesspools and septic tanks produced by the municipality and discharged into the Itumbiara Wastewater Treatment Plant (WWTP), already working at its full capacity. Statistical tests have proved that wastes from cesspool and septic tanks disposed into UASB reactors showed no significant difference in the final effluent quality. It was not evidenced also significant differences in the operation and maintenance of the reactors. The biological sludge from the UASB reactors got stable after being added the wastes (ratio VS/TS between 0.53 and 0.58 average). The receiving reactor’s begs had a worse efficiency but statistical tests showed that the difference was not significant when compared to the control reactors. It was observed in this study, there is no need for the pre-flotation of waste before being released at WWTP with UASB system. Thus the UASB is a viable alternative, but it is necessary to follow a protocol to establish criteria such as the waste application rate, the WWTP site for waste discharge, physical structure and people, as well as to choose for relevant parameters for the waste monitoring before co-treatment.